Assessment of Eco-Physiological Performance of Quercus ilex L. Leaves in Urban Area by an Integrated Approach - Arena, Carmen; De Maio, Anna; De Nicola, Flavia; Santorufo, Lucia; Vitale, Luca; Maisto, Giulia (WATER AIR AND SOIL POLLUTION, 2014)
Plant physiological performance may be endangered in contaminated urban areas. Metal and polycyclic aromatic hydrocarbon (PAH) content in Quercus ilex leaves mainly reflects air pollution, being for these pollutants traceable the translocation from soil. In this work, in a field study, the responses at structural and functional level of Q. ilex leaves to metal and PAH pollution were assessed by an integrated approach. At this purpose, morphological (functional traits), biochemical (pigment content, antioxidant capacity, and PARP activity), and physiological (partitioning of absorbed light in the photosynthetic process) analyses were performed in leaves collected at urban parks and roadsides. Compared to the leaves of the urban parks, those sampled at the roadsides showed higher metal and PAH accumulation. The most contaminated leaves showed smaller leaf sizes and lower relative water and pigment content, as well as a lower photochemistry. In this circumstance, the excess of absorbed light at PSII was mainly dissipated via non-regulated than heat processes. On the basis of the biochemical analyses, the occurrence of DNA damages in contaminated Q. ilex leaves may be hypothesized.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: PAH and metal contamination; PARP activity; Photochemistry; Q. ilex

Detection of hybrids in nature: application to oaks (Quercus suber and Q. ilex). - Burgarella, C.; Lorenzo, Z.; Jabbour-Zahab, R.; Lumaret, R.; Guichoux, E.; Petit, R. J.; Soto, A.; Gil, L. (Heredity, 2009)
Powerful and accurate detection of first-generation (F1) hybrids and backcrosses in nature is needed to achieve a better understanding of the function and dynamics of introgression. To document the frequency of ongoing interspecific gene exchange between two Mediterranean evergreen oaks, the cork oak (Quercus suber) and the holm oak (Q. ilex), we analyzed 1487 individuals originating from across the range of the two species using eight microsatellite loci and two Bayesian clustering approaches (implemented in the programs STRUCTURE and NEWHYBRIDS). Simulated data were used to assess the differences between the two clustering methods and to back up the choice of the threshold value for the posterior probability to discriminate admixed from pure individuals. We found that the use of STRUCTURE resulted in the highest power to detect hybrids, whereas NEWHYBRIDS provided the highest accuracy. Irrespective of the approach, the two species were clearly distinguished as independent genetic entities without any prior information. In contrast with previous reports, we found no evidence for unidirectional introgression. The overall hybridization rate was very low (<2% of introgressed individuals). Only two individuals were identified as F1 hybrids and five as early backcrosses. This work shows that the combined application of the two complementary Bayesian approaches and their systematic validation with simulations, fit for the case at hand, helps gain resolution in the identification of admixed individuals.
The following values have no corresponding Zotero field: accession-num: 19240752
Keywords: clustering analysis; introgressive hybridization; microsatellites; Q. ilex; Quercus suber; Simulation

Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C.; Vitale, L.; Virzo De Santo, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819doi: 10.1080/11263500802410819The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold

Biomass, nutrient content, litterfall and nutrient return to the soil in Mediterranean oak forests - Rapp, Maurice; Santa Regina, Ignacio; Rico, Mercedes; Gallego, Humberto Antonio (Forest Ecology and Management, 1999)
We estimated above-ground biomass, nutrient content, litterfall and nutrient return to the soil in deciduous and evergreen Quercus pyrenaica Will., Quercus lanuginosa Lamk and evergreen Quercus ilex L. oak forests, respectively, near Salamanca (Spain) and Montpellier (France). The calculated biomass ranged from 64 to 121 Mg ha ÿ1 . Perennial material (trunks and branches) represented 96±97% in the four Spanish Q. pyrenaica stands and 93% in the French Q. lanuginosa and Q. ilex stands. Q. pyrenaica had higher P, Mg, Fe and Mn contents than the other two species from southern France. In contrast, these latter species had higher N and Ca concentrations. All of these differences were related to soil nutrient availability, especially Ca, Mg, P, Fe and Mn. Comparison of the chemical composition of leaves on trees with that of leaf litter indicated retention and translocation of N, P and K from leaves to perennial biomass and recycling of Ca and Mg from trees to the soil
Keywords: forest biomass; forest ecosystems; litterfall; Q. ilex; Q. lanuginosa; Q. pyrenaica